Steps Toward a Universal Grammar of Dance: Local Grouping Structure in Basic Human Movement Perception - Charnavel, Isabelle (Frontiers in Psychology, 2019)
The general goal of this paper is to investigate the structure of our unconscious mental representation of dance: we do not perceive dance as an unanalyzed flow of movement, but we unconsciously create a mental representation regulated by structural principles. Specifically, this article examines local grouping principles in dance perception inspired by Lerdahl & Jackendoff’s 1983 approach to musical grouping. I spell out the basic perceptual dimensions at work in basic human movement perception, and on that basis, I propose six principles of change that determine group boundaries in dance (change of body part, orientation, level, direction, speed, quality). I experimentally test the relevance and interaction of these principles, and find that they are organized on a scale of relative strength. This experiment thus supports the hypothesis that grouping is a general cognitive capacity applying across domains and modalities, and shows how specific grouping principles are stated in relation to modality-specific and domain-specific dimensions. More generally, it takes a step toward the development of a generative theory of dance that should help extend the research avenue of comparing complex temporal cognitive activities across modalities (visual, auditory) and purposes (referential, non-referential), which so far involves spoken language, signed language and music.